Induced roll magnetic separator applied for high grade ilmenite separation from mining tailing - Wiwik Dahani; Rita Sundari; Subandrio Somali; Irfan Marwanza; Andriyani Andriyani; Djoko Hartanto; Khuzaimah Arifin; Ratna Ediati (Universitas Mercu Buana, 2023)
This article aimed to separate ilmenite (FeTiO3) mineral from tin tailing applying a single splitter IRMS (Induced Roll Magnetic Separator). Ilmenite mineral is the substantial main source for TiO2. This work used air table middling for feeding. The mineral components of middling feeding from air table using grain counting analysis were found as follows: cassiterite (48.61%), ilmenite (21.36%), monazite (18.56%), pyrite (4.60%), zircon (5.85%), quartz (0.71%), anatase (0.27%), and tourmaline (0.02%), It was found that electrical current and opening of single splitter affected the degree of separation addressing to ilmenite recovery and ilmenite grade. The finding showed that current of 15 Ampere and single splitter with opening 4.25 cm yielded ilmenite recovery more than 74%. The high grade ilmenite (90.46 %) and recovery of 29.38% was obtained using 5 Ampere with single splitter opening of 1.0 cm. Up to date, the study on ilmenite separation from tailing only focused on the effect of current, however, the effect of single splitter magnetic separator to enhance ilmenite recovery from other paramagnetic minerals such as monazite, siderite, xenotime and tourmaline has not yet been reported.